2006
DOI: 10.1097/01.moo.0000193177.62074.fd
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis and bacterial biofilms

Abstract: Progress in the treatment of nasal and paranasal sinus cancers could be achieved through better prevention and the developments of more selective treatments such as endoscopic resection, high-precision radiotherapy, and new chemotherapy drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 67 publications
1
55
0
6
Order By: Relevance
“…Coughing and choking (laryngospasm) [7] can be induced by direct refluxate irritation, because the sensitivity in laryngeal sensory endings is up regulated by local inflammation [11,12]. LPR seems to be more common than previously reported in the literature [2], as the present study identified that 18% of patients attending an ENT outpatient department benefited from anti-reflux treatment. The male to female patient ratio was, however, equal, in keeping with previous reports [13].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Coughing and choking (laryngospasm) [7] can be induced by direct refluxate irritation, because the sensitivity in laryngeal sensory endings is up regulated by local inflammation [11,12]. LPR seems to be more common than previously reported in the literature [2], as the present study identified that 18% of patients attending an ENT outpatient department benefited from anti-reflux treatment. The male to female patient ratio was, however, equal, in keeping with previous reports [13].…”
Section: Discussionmentioning
confidence: 59%
“…In addition, it presents with usually normal oesophageal motility, and most patients do not have oesophagitis as is always the case in GERD [6]. Nevertheless, different research groups have proposed different theories for the pathogenesis of LPR, considering it either as a retrograde flow of gastric contents to the laryngopharynx [2], or an abnormal presence of gastric contents above level of the upper oesophageal sphincter [7]. Heterotrophic gastric mucosa in the cervical oesophagus could also play a role in the pathogenesis of LPR, at least in the minor group of patients with laryngitis of the posterior larynx [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical history and laryngeal examination constitutes the main diagnostic approach for LPR according to most otolaryngologists [1,2]. For this purpose, a self-administered tool, the reflux symptom index and an 8-item clinical severity scale (reflux finding score: RFS), both of which were introduced by Belafsky et al [3,4], are widely used in LPR patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…15 • Surgical management: Laproscopic or Nissen fundoplication is a well-established surgical treatment for GERD and produces reliable and reproducible results. 16 However, its role in the management of LPR is uncertain.…”
Section: Treatmentmentioning
confidence: 99%